Rate of Clinical Complete Response for 1 Year or More in Bone-Metastatic Breast Cancer after Comprehensive Treatments including Autologous Formalin-Fixed Tumor Vaccine - Fumito Kuranishi; Yuki Imaoka; Yuusuke Sumi; Yoji Uemae; Hiroko Yasuda-Kurihara; Takeshi Ishihara; Tsubasa Miyazaki; Tadao Ohno (International Journal of Breast Cancer)
Introduction. No effective treatment has been developed for bone-metastatic breast cancer. We found 3 cases with clinical complete response (cCR) of the bone metastasis and longer overall survival of the retrospectively examined cohort treated comprehensively including autologous formalin-fixed tumor vaccine (AFTV). Patients and Methods. AFTV was prepared individually for each patient from their own formalin-fixed and paraffin-embedded breast cancer tissues. Results. Three patients maintained cCR status of the bone metastasis for 17 months or more. Rate of cCR for 1 year or more appeared to be 15% (3/20) after comprehensive treatments including AFTV. The median overall survival time (60.0 months) and the 3- to 8-year survival rates after diagnosis of bone metastasis were greater than those of historical control cohorts in Japan (1988–2002) and in the nationwide population-based cohort study of Denmark (1999–2007). Conclusion. Bone-metastatic breast cancer may be curable after comprehensive treatments including AFTV, although larger scale clinical trial is required.